2022
DOI: 10.1200/jco.2022.40.16_suppl.e18725
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of SARS-CoV-2 vaccines and booster doses in patients with cancer: An analysis from the European OnCovid registry.

Abstract: e18725 Background: Immunogenicity and safety of SARS-CoV-2 vaccines have been widely investigated in patients (pts) with cancer. However, their effectiveness against Coronavirus disease 2019 (COVID-19) and the additional protective effect of a booster dose in this population are yet to be defined. Methods: Using OnCovid study data (NCT04393974), a European registry enrolling consecutive pts with cancer and COVID-19, we evaluated morbidity and 14 days case fatality rates (CFR14) from COVID-19 in pts who were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The following covariates were used: country (the UK vs Spain vs Italy), sex (male vs female), number of comorbidities (0-1 vs ≥2), primary tumour, tumour stage at COVID-19 diagnosis (advanced vs non-advanced), tumour status at COVID-19 diagnosis (active vs non-active), receipt of systemic anticancer therapy within 4 weeks before COVID-19 diagnosis (yes vs no), and age with the 65 years cutoff that has been concordantly used in our registry (≥65 vs <65 years). [7][8][9][10]13,14 To obtain more balanced models, we included variables with missing data by grouping them as reference term in case of a less than 5% of missingness and as an "unknown" category in case of a 5% or more of missingness. Last, in view of the fact that sequelae evaluation and assessments were not predefined across centres, and that the data source consisted of 20 different institutions, all 95% CIs for COVID-19 sequelae comparisons were corrected following a clustered-robust adjustment for participating centre.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following covariates were used: country (the UK vs Spain vs Italy), sex (male vs female), number of comorbidities (0-1 vs ≥2), primary tumour, tumour stage at COVID-19 diagnosis (advanced vs non-advanced), tumour status at COVID-19 diagnosis (active vs non-active), receipt of systemic anticancer therapy within 4 weeks before COVID-19 diagnosis (yes vs no), and age with the 65 years cutoff that has been concordantly used in our registry (≥65 vs <65 years). [7][8][9][10]13,14 To obtain more balanced models, we included variables with missing data by grouping them as reference term in case of a less than 5% of missingness and as an "unknown" category in case of a 5% or more of missingness. Last, in view of the fact that sequelae evaluation and assessments were not predefined across centres, and that the data source consisted of 20 different institutions, all 95% CIs for COVID-19 sequelae comparisons were corrected following a clustered-robust adjustment for participating centre.…”
Section: Discussionmentioning
confidence: 99%
“…Limited, but plausible, evidence suggests that previous SARS-CoV-2 vaccination might reduce the prevalence of COVID-19 sequelae in patients with cancer. 10 However, novel SARS-CoV-2 variants are capable of evading vaccinal immunity, and new vaccines have now been developed to overcome immune evasion. 11,12 Although recent evidence suggests that overall SARS-CoV-2 infections diagnosed during the outbreak of the omicron (B.1.1.529) variant are associated with improved COVID-19 outcomes in comparison to previous phases of the pandemic, 13 we showed that improvement in mortality was mainly driven by previous vaccinal immunity, arguing against the hypothesis of an inherently reduced pathogenicity of the omicron variant in patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Due to substantial heterogeneity in terminology used to assess symptoms/conditions, both via clinical diagnoses and patient-reported methods, outcomes in this SLR were extracted verbatim before grouping by organ and system class to facilitate analyses. Existing approaches in the literature and medical specialists were consulted 19–22. Individual symptoms and conditions were grouped by domains, as described in online supplemental table 5.…”
Section: Methodsmentioning
confidence: 99%
“…Thirty-two studies met the inclusion criteria [14][15][16][17] and were included in the final review (Table 1). All studies were nonrandomized [14][15][16][17] ; of these, fourteen were retrospective cohort studies, 15,25,[29][30][31]35,36,40,[44][45][46]48,49,51 nine were prospective cohort studies 14,16,28,32,34,37,38,41,50 , five were cross-sectional studies, 17,24,42,43,47 and four were case-control studies. 26,27,33,39 One of the cross-sectional studies was also within a prospective cohort study.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%